2005
DOI: 10.1080/09670260500150511
|View full text |Cite
|
Sign up to set email alerts
|

Fine-structure of the vegetative frustule, perizonium and initial valve ofAchnanthes yaquinensis(Bacillariophyta)

Abstract: This study clarifies the fine structure of the vegetative and initial valves of Achnanthes yaquinensis and briefly compares them to other Achnanthes species. It also elucidates the structure of the perizonium, based on auxospore development in short-term cultures. The araphid valve has marginal ridges and terminal spines that allow connecting valves to form a chain. The terminal spines develop from the rapheless sternum. The complete cingulum consists of 3-5 split bands with two rows of areolae. These features… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 28 publications
(25 reference statements)
1
29
0
Order By: Relevance
“…We believe, however, that some of the LP bands were hidden by folding of the auxospore, which seems likely because all of the longitudinal perizonia reported so far in pennate diatoms are structurally symmetrical (e.g. von Stosch 1962Stosch , 1982Mann 1982b;Toyoda et al 2005), even in Amphora (Nagumo 2003). There would therefore be five longitudinal bands in P. oceanica (Fig.…”
Section: Auxosporulation and Auxospore Fine Structurementioning
confidence: 77%
See 1 more Smart Citation
“…We believe, however, that some of the LP bands were hidden by folding of the auxospore, which seems likely because all of the longitudinal perizonia reported so far in pennate diatoms are structurally symmetrical (e.g. von Stosch 1962Stosch , 1982Mann 1982b;Toyoda et al 2005), even in Amphora (Nagumo 2003). There would therefore be five longitudinal bands in P. oceanica (Fig.…”
Section: Auxosporulation and Auxospore Fine Structurementioning
confidence: 77%
“…The TP bands combine to form a cigar-shaped perizonium with a narrow ventral suture, beneath which there is often a set of LP bands, again differentiated into a central primary band and two short flanking series of secondary bands (e.g. Mann 1982b;Mann & Stickle 1993;Nagumo 2003;Sato et al 2004;Toyoda et al 2005). The function of the perizonium appears to be to support and constrain anisometric expansion of the auxospore (Mann 1994).…”
Section: Auxosporulation and Auxospore Fine Structurementioning
confidence: 99%
“…Williams & Round (1986: 324) (Sato et al 2008a), and in the biraphid diatoms, S. marvanii, D. papula, C. linearis and F. tenera (this study). In monoraphid diatoms Achnanthes crenulata Grunow in Cleve & Grunow (1880: 20) (Toyoda et al 2005) and Achnanthes yaquinensis McIntire & Reimer (1974: 174) (Toyoda et al 2006), however, scales were not present. Also, the transverse perizonial bands were not present in the two monoraphid species.…”
Section: Ultrastructure Of Incunabula and Perizoniummentioning
confidence: 96%
“…The ultrastructure of a perizonium in pennate diatoms has been reported in many species covering araphid (Sato et al 2004, Sato et al 2008a and raphid diatoms (Mann 1982, Toyoda et al 2005, Poulíčková & Mann 2006, Toyoda et al 2006, Kaczmarska et al 2007, Poulíčková et al 2007, Mann & Poulíčková 2009, Mann et al 2011. It also has been suggested that the ultrastructure of the perizonium has phylogenetic significance at higher taxonomic levels (Medlin & Kaczmarska 2004).…”
Section: Introductionmentioning
confidence: 99%
“…While diatom capsules have mostly been characterised biochemically, electron microscopical analyses was so far focussed on the morphology of diatom frustules (Toyoda et al, 2005(Toyoda et al, , 2006Morin, Coste & Hamilton, 2008) and the development of its morphological variations as environmental markers (Potapova & Hamilton, 2007;Hlúbiková, Ector & Hoffmann, 2011;Cantonati et al, 2014). In the present study, scanning electron microscopy (SEM), as well as energy-dispersive X-ray (EDX) spectroscopy were employed to analyse the microstructure and development stages of Achnanthidium minutissimum capsules in order to further develop this species as a model system for diatom-bacteria interactions, and to elucidate one aspect of the complex interactions of diatoms and other micro-organisms.…”
Section: Introductionmentioning
confidence: 99%